Act of May 28, 1746, ch. X, Acts and Laws of Mass. Bay, p. 208 - (:unkn) unknown (General Publisher, 1746)
Prohibited the indiscreet firing of any gun or pistol in the town under penalty of forty shillings.
--
Keywords: DISCHARGE